Weed community in a conventionally-grown Olive orchard vs. weed community in consociation with pyrethrum (Tanacetum cinerariifolium (Trevir.) Sch. Bip.) - Štefanić, Edita (Array, 2021)
On the experimental plots of the Institute of Agriculture and Tourism in Poreč, weed communities were analyzed in a conventionally grown olive orchard and in consociation with pyrethrum. Phytocenological surveys were conducted in March, June, and September using the Braun-Blanquet Cover Abundance Scale. Altogether, 54 species of vascular plants were recognized in both orchards. However, in a conventionally grown olive orchard, 27 were identified, whereas 42 weed species were identified in consociation with pyrethrum. Only 15 weeds were common to both orchards. Between both olive orchards, significant differences existed regarding the floristic and community diversity metrics. In consociation with pyrethrum as a cover crop, olive orchard had a more stable weed community during the season, while two weed species, Mercurialis annuua L. and Medicago arabica (L.) Huds., dominated in a conventionally grown orchard in the fall. The weed communities in both orchards significantly differ considering the appearance season (spring, summer, and fall). An autumnal weed community in a conventionally grown olive orchard was more diverse, more abundant, and with a more distinct floristic composition than a weed community in the spring and summer periods. However, an olive‐orchard weed community in consociation with pyrethrum also differed regarding the season, but a Canonical Correspondence Analysis (CCA) demonstrated a clear separation of a more diverse estival weed community than the one observed in the spring and summer.